2022
DOI: 10.1111/imj.15942
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in Australia and New Zealand Nephrology: basic science and gender equity in peril

Abstract: Basic science research remains fundamental to progress in clinical care, understanding of disease pathophysiology and underpinning the evolution of personalised medicine. Exposure to research is pivotal to educating students, but a declining profile of basic science research has the potential to erode research capacity further. The capacity for women to engage in research and remain in academia long term is continually challenged by negative gender-based experiences and institutional barriers. The authors expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…In the first study, themes and authorship of broad research area within abstracts published during 2005-2020 Annual Scientific Meetings of the Transplantation Society of Australia and New Zealand (TSANZ) and Australia and New Zealand Society of Nephrology (ANZSN) were explored. 1 Rogers et al reported an increase in nonbasic science research abstracts, and female first authors of those abstracts during this time, although there were proportionately fewer female presenters of basic science research. 1 The total number of abstracts over time or the definition of abstract role seniority was not clearly defined, either by advanced technical expertise, hierarchies of competency, years in the industry or professional role assignment.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In the first study, themes and authorship of broad research area within abstracts published during 2005-2020 Annual Scientific Meetings of the Transplantation Society of Australia and New Zealand (TSANZ) and Australia and New Zealand Society of Nephrology (ANZSN) were explored. 1 Rogers et al reported an increase in nonbasic science research abstracts, and female first authors of those abstracts during this time, although there were proportionately fewer female presenters of basic science research. 1 The total number of abstracts over time or the definition of abstract role seniority was not clearly defined, either by advanced technical expertise, hierarchies of competency, years in the industry or professional role assignment.…”
Section: Introductionmentioning
confidence: 91%
“…Physician qualities are humanistic, and practices are accountable to peer and societal expectations. We discuss two studies, by Rogers et al 1 and Francis et al, 2 published in this issue of the Internal Medicine Journal. Using different research methods, each having recognised limitations, the role of worker inequality with gender, ethnicity, professional role and leadership was examined.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations